Paket Aktivitas Fisik Olahraga dalam Meningkatkan Kelekatan Ibu dan Anak pada Masa Social Distancing - Cholid, abd; Ervin Nurul Affrida (incrementapedia, 2021)
Social distancing has an impact for all activities implemented at home so that parents are expected become stimulants to achieve children's development tasks. Therefore we need a model of sport physical activity to increase bonding between mother and child during the social distancing because Covid-19 pandemic. The research method used development research. The results of acceptability assessment from package I include of usability aspect with a mean score of 85.93%, the convenience aspect of 88.28%, the accuracy aspect of 88.22% and the appropriateness aspect of 88.85%. Furthermore, package II includes of usability aspects of 85.93%, the convenience aspect of 88.28%, the accuracy aspect of 88.22% and the appropriateness aspect of 88.85%. The assessment is sourced from expert tests, product-user candidate tests and field tests so it can be concluded that the I and II packages are very good and dont need to be revised. The result of effectiveness product test showed that mean pre-test score (XB) was 655 and the post-test mean score (XA) was 712, so that XA>XB. The results of pre-test and post-test scores seen in the binomial test table obtained p = 0.004 when compared with the t table value at the 5% significance level, 0.004 <0.05, so it can be concluded that physical sports activity package is effective to increase bonding between mothers and children at social distancing period.